New Bioanalytical Method Development and Validation for Extraction of Mirabegron in Human Plasma by using Quechers Method and Liquid ChromatographyTandem Mass Spectrometry (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: To develop and validate a sensitive, robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for quantifying Mirabegron in K2EDTA human plasma, ensuring suitability for routine analytical applications. Materials and Methods: Employing a C18 column and an isocratic mobile phase, achieving excellent chromatographic resolution of mirabegron was achieved. Plasma samples were prepared using the QuEChERs extraction technique, ensuring efficient sample cleanup and consistent recovery. Mirabegron D5 served as the internal standard, closely matching the analyte in terms of extraction efficiency and chromatographic behavior. The autosampler temperature was set at 5°C with a total run duration of 4.5 min. Mirabegron and its internal standard exhibited a retention time of 2.05 min. Results and Discussion: The QuEChERs extraction technique met all validation criteria, demonstrating a mean recovery of 79.44% for mirabegron and 78.74% for the internal standard. The calibration curve was linear over 0.201–100.677 ng/mL (r2 = 0.9976), with a lower limit of quantification of 0.201 ng/mL, confirming high sensitivity. The method’s simplicity, robustness, and rapid analysis time underscored its applicability for high-throughput studies. Conclusion: The validated LC-MS/MS method proved effective, simple, and robust, making it well-suited for routine pharmacokinetic and bioequivalence studies of mirabegron in human plasma.